Humanized Mouse Models of Staphylococcus aureus Infection - Parker, Dane (Frontiers in Immunology, 2017)
Staphylococcus aureus is a successful human pathogen that has adapted itself in response to selection pressure by the human immune system. A commensal of the human skin and nose, it is a leading cause of several conditions: skin and soft tissue infection, pneumonia, septicemia, peritonitis, bacteremia and endocarditis. Mice have been used extensively in all these conditions to identify virulence factors and host components important for pathogenesis. Although significant effort has gone towards development of an anti-staphylococcal vaccine, antibodies have proven ineffective in preventing infection after successful studies in mice. These results have raised questions as to the utility of mice to predict patient outcome and suggest that humanized mice might prove useful in modeling infection. The development of humanized mouse models of S. aureus infection will allow us to assess the contribution of several human-specific virulence factors, in addition to exploring components of the human immune system in protection against S. aureus infection. Their use is discussed in light of several recently reported studies.